2009
DOI: 10.1002/bip.21147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics (MD) simulations of VIP and PACAP27

Abstract: Vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptide-27 (PACAP27) are members of the secretin-glucagon family containing 28 and 27 residues, respectively. NMR spectroscopy studies suggest that the N-terminus exhibit consecutive beta-turns whereas the central and C-terminal parts of the VIP molecule have been characterized as being two alpha-helices. In contrast, similar studies carried out on PACAP suggest that the shortest active peptide segment PACAP27 in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, given the significantly reduced dimensionality of onedimensional (1D) profiles or smooth 2D landscapes, the roughness of the protein-folding landscape, and the heterogeneous nature of protein-folding pathways, it can be difficult to ascertain detailed and important features of protein folding from these simple representations (3). As more and more successful folding simulations are being reported (4)(5)(6)(7)(8)(9)(10)(11), it is becoming more urgent to find effective ways to present protein folding.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the significantly reduced dimensionality of onedimensional (1D) profiles or smooth 2D landscapes, the roughness of the protein-folding landscape, and the heterogeneous nature of protein-folding pathways, it can be difficult to ascertain detailed and important features of protein folding from these simple representations (3). As more and more successful folding simulations are being reported (4)(5)(6)(7)(8)(9)(10)(11), it is becoming more urgent to find effective ways to present protein folding.…”
Section: Introductionmentioning
confidence: 99%
“…Structural analysis has shown that the N-terminus of PACAP (HSDGI) is flexible and disordered [21] , while C*HSDGIC* synthesized from cyclizing HSDGI and adding two Cys residues at both ends is more stable with a more fixed conformation. Furthermore, CHC has a small molecular weight (approximately 700 Da), which allows it to easily penetrate the blood-retina barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The implicit solvent approach essentially reduces solvent friction and has been shown to enhance conformational sampling for a wide variety of peptide, protein, and nucleic acid systems [9597], and more recently, larger protein systems [98, 99]. Correspondence between GB models and experimentally derived structures has also been established [100, 101], which, similar to AMD, makes it a good choice for extensions of the computational receptor ensemble.…”
Section: Current Challenges and Opportunitiesmentioning
confidence: 99%